2020
DOI: 10.3389/fcvm.2020.586871
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Diagnostic Gene Biomarkers Associated With Immune Infiltration in Patients With Acute Myocardial Infarction

Abstract: The present study was designed to identify potential diagnostic markers for acute myocardial infarction (AMI) and determine the significance of immune cell infiltration in this pathology. Methods: Two publicly available gene expression profiles (GSE66360 and GSE48060 datasets) from human AMI and control samples were downloaded from the GEO database. Differentially expressed genes (DEGs) were screened between 80 AMI and 71 control samples. The LASSO regression model and support vector machine recursive feature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 45 publications
(48 reference statements)
1
81
0
Order By: Relevance
“…Increasing evidence indicated that the immune system plays a vital role in malignancy initiation, cancer progression, and cancer therapeutic responses. Immune cells have been confirmed to have a significant influence on various disease processes, including cancer progression [21][22][23]. So far, immunotherapies in OC are remaining in the exploratory stages.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence indicated that the immune system plays a vital role in malignancy initiation, cancer progression, and cancer therapeutic responses. Immune cells have been confirmed to have a significant influence on various disease processes, including cancer progression [21][22][23]. So far, immunotherapies in OC are remaining in the exploratory stages.…”
Section: Discussionmentioning
confidence: 99%
“…The algorithm calculated the supposed immune cells' abundance by using a comparison range of 1000 permutations of 22 immune cell subtypes (LM22) [ 23 ]. In order to determine immune violations of each sample, we used the mRNA expressions matrix as input files [ 24 ]. CIBERSORT production of p < 0.05 was filtered for subsequent study, indicating inferred proportion of CIBERSORT generated immune cell number is precise [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The algorithm estimated the putative abundance of immune cells using a reference set with 22 immune cell subtypes (LM22) with 1,000 permutations (Newman et al, 2015 ). We used the mRNA expression matrix as the input files to evaluate the immune infractions of each sample through the CIBERSORT algorithm (Zhao et al, 2020 ). Cases with a CIBERSORT output of P < 0.05, demonstrating that the inferred proportions of immune cell populations produced by CIBERSORT are accurate (Ali et al, 2016 ), were filtered out for subsequent analysis.…”
Section: Methodsmentioning
confidence: 99%